Development a Rain Sensor With Alarm System - Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2023)
The Water Rain Sensor with Alarm is a technology device that detects and alerts users when rainfall is present. It aims to provide an early warning system for potential dried clothes on a clothesline or flooding in a variety of locations, especially properties. This abstract highlights the Water Rain Sensor with Alarm's primary features and functionalities. The Water Rain Sensor detects the presence of rainwater using advanced sensor technologies. It has high-precision moisture sensors strategically located in places prone to water collection, such as roofs. These sensors constantly monitor the moisture levels in their surroundings and immediately sound an alarm if they detect an abnormal increase, showing the presence of rains.The alarm systems built into the Water Rain Sensor is an efficient way of informing consumers about dry clothes on a clothesline or flooding issues. When the rain sensors detect rainwater, the alarm is triggered, emitted a loud sound, and visual indicators are displayed to draw quick attention. The alarm acts as an early warning system, allowing users to take immediate action to prevent the cloth from keep drying, save precious items, and secure the safety of others on the premises.Additional features are included to improve the utility and convenience of the Water Rain Sensor with Alarm. Wireless connectivity capabilities, for example, allow customers to receive real-time notifications on their smartphones or other linked devices. The sensor's data can be transmitted by Wi-Fi or a dedicated mobile application, allowing users to know whether there is rain or no rain and to switch off the alarm straight from their phone, even when they are not near the place.